Permafrost Dynamics and Degradation in Polar Arctic From Satellite Radar Observations, Yamal Peninsula - Teshebaeva, Kanayim; van Huissteden, Ko J.; Echtler, Helmut; Puzanov, Alexander V.; Balykin, Dmitry N.; Sinitsky, Anton I.; Kovalevskaya, Nelley M.; Dolman, Han A. J. (Frontiers in Earth Science, 2021)
We investigate permafrost surface features revealed from satellite radar data in the Siberian arctic at the Yamal peninsula. Surface dynamic analysis based on SRTM and TanDEM-X DEMs show up to 2 m net loss of surface relief between 2000 and 2014 indicating a highly dynamic landscape. Surface features for the past 14 years reflect an increase of small stream channels and a number of new lakes that developed, likely caused by permafrost thaw. We used Sentinel-1 SAR imagery to measure permafrost surface changes. Due to limited observation data we analyzed only two years. The InSAR time-series has detected surface displacements in three distinct spatial locations during 2017 and 2018. At these three locations, 60-120 mm/yr rates of seasonal surface permafrost changes are observed. Spatial location of seasonal ground displacements align well with lithology. One of them is located on marine sediments and is linked to anthropogenic impact on permafrost stability. Two other areas are located within alluvial sediments and are at the top of topographic elevated zones. We discuss the influence of the geologic environment and the potential effect of local upwelling of gas. This combined analyses of InSAR time series with analysis of geomorphic features from DEMs present an important tool for continuous process monitoring of surface dynamics as part of a global warming risk assessment.